2022
DOI: 10.1002/aenm.202203188
|View full text |Cite
|
Sign up to set email alerts
|

Pulse High Temperature Sintering to Prepare Single‐Crystal High Nickel Oxide Cathodes with Enhanced Electrochemical Performance

Abstract: is still the most popular cathode material in the LIBs for 3C products, mainly owing to its extraordinarily high tap density, [2] since there is a stricter requirement on the volumetric energy density. To reduce the amount of high-cost Co, part of Co was substituted by Ni and Mn with the generation of Li(Ni x Co y Mn z )O 2 (NCM, x + y + z = 1), which not only improves the structural and thermal stability but also allows more reversible extraction-intercalation of Li + and so endows more capacity, making it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…[85] It is observed that with the ascending of Sr content and the rise of Li/TM ratio and the increase of sintering temperature, the particle size keeps growing progressively (Figure 8a). Similar to other reports, [11] with the increment of SC-NCM particle size, the Li + /Ni 2+ disorder rates are gradually increased. For instance, the Li + /Ni 2+ disorder rate was only 2.7% for SC-D1, but it progressively grew to 3.9%, 4.6%, 5.0%, and 5.1% for SC-D3, SC-D5, SC-D7, and SC-D9 samples, respectively.…”
Section: Strategies For Tuning Particle Sizesupporting
confidence: 89%
See 3 more Smart Citations
“…[85] It is observed that with the ascending of Sr content and the rise of Li/TM ratio and the increase of sintering temperature, the particle size keeps growing progressively (Figure 8a). Similar to other reports, [11] with the increment of SC-NCM particle size, the Li + /Ni 2+ disorder rates are gradually increased. For instance, the Li + /Ni 2+ disorder rate was only 2.7% for SC-D1, but it progressively grew to 3.9%, 4.6%, 5.0%, and 5.1% for SC-D3, SC-D5, SC-D7, and SC-D9 samples, respectively.…”
Section: Strategies For Tuning Particle Sizesupporting
confidence: 89%
“…Based on these considerations, very recently, Zhou and Qiu proposed a PHTS to prepare SC-NCM90 and SC-NCM80 materials. [11] It has been demonstrated that the Li-loss start to be serious at higher than 950 °C, which is also the lowest single crystalline growth temperature and is widely used in CHTS. In PHTS, on the basis of the traditional calcination procedure for ensuring phase generation, an additional shortterm higher temperature process was introduced as a pulse heating for primary particles' fusion, in which, the applied temperature is ≈150 °C higher than that used in CHTS and is ≈300 °C higher than the temperature used in preparing PC-NCM.…”
Section: Phts Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, both the concentration of OVs and particle morphology are correlated to the parameters of the sintering process, such as the temperature, time, and atmosphere. For example, Zhou et al prepared octahedral particles through nonisothermal sintering . Cui et al proposed a temperature swing-like sintering strategy with a heating and cooling rate of 0.125 °C min –1 to stabilize the lattice oxygen .…”
Section: Introductionmentioning
confidence: 99%